2011
DOI: 10.1093/ejechocard/jer108
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and reliability of point-of-care pocket-sized echocardiography

Abstract: AimsTo study the reliability and feasibility of point-of-care pocket-sized echocardiography (POCKET) at the bedside in patients admitted to a medical department at a non-university hospital.Methods and resultsOne hundred and eight patients were randomized to bedside POCKET examination shortly after admission and later high-end echocardiography (HIGH) in the echo-lab. The POCKET examinations were done by cardiologists on their ward rounds. Assessments of global and regional left ventricular (LV) function, right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 16 publications
(20 reference statements)
7
121
0
3
Order By: Relevance
“…The use of the PSE to visualize left ventricular wall motion and systolic function has been previously evaluated. Several studies have demonstrated that the PSE can obtain interpretable images in the vast majority (85-100%) of patients by inexperienced sonographers, in both the inpatient and outpatient settings [10][11][12]. A complete sTTE study takes approximately 20-25 minutes to acquire, with a standard echocardiography machine costing approximately four times that of a PSE machine [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the PSE to visualize left ventricular wall motion and systolic function has been previously evaluated. Several studies have demonstrated that the PSE can obtain interpretable images in the vast majority (85-100%) of patients by inexperienced sonographers, in both the inpatient and outpatient settings [10][11][12]. A complete sTTE study takes approximately 20-25 minutes to acquire, with a standard echocardiography machine costing approximately four times that of a PSE machine [20].…”
Section: Discussionmentioning
confidence: 99%
“…Its size confers the advantage of portability, making PSE ideal for point-of-care evaluation, either at the bedside, or in the outpatient setting. Previous studies have examined the diagnostic accuracy of PSE, its potential clinical applications, and the training involved to maximize safety and effectiveness of its use [7][8][9][10][11]. Several studies have reported that PSE can qualitatively assess LVEF with good reliability, even when a sonographic trainee acquires and/or interprets images [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Bedside cardiac ultrasound imaging allows a reliability and accuracy comparable to standard echocardiography to evaluate cardiac dimensions, significant systolic dysfunction and pericardial effusion 7,23,24 even when performed by non cardiologist 25,26 or medical residents 6,27 after a short training period and using miniaturized ultrasound devices.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…24 Moreover despite the obvious limits of a gross evaluation, different studies showed that bedside echocardiography is definitely superior to physical examination in the detection of valvular regurgitation. 28,29 Heterogeneous results regarding the modality and duration of training for bedside echocardiography have been obtained through different teaching protocols applied to medical students or residents.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…Pocket-sized ultrasound devices are powerful tools that have been found to perform similarly to traditional high-end systems when used by experienced clinicians. [5][6][7][8][9][10][11][12][13] Internal medicine residents desire ultrasound training, but self-reported competence is low. 14 Several studies have shown that after brief training, residents can become competent in performing and interpreting basic ultrasound examinations.…”
Section: Introductionmentioning
confidence: 99%